Cryptogenic stroke in a 5-year-old girl with patent foramen ovale: A rare case - Dimiati, Herlina; Rasaki, Rico; Haypheng, Te (Narra Sains Indonesia, 2024)
Stroke ranks among the prevalent factors contributing to child mortality. Cryptogenic stroke has been linked with patent foramen ovale (PFO), which has been suggested as a possible route for thrombus, gas bubble, or another particulate that comes through systemic venous circulation to the brain artery. Yet, the most effective approach for managing cryptogenic stroke involving a PFO remains uncertain. This case aims to report a PFO patient with complications of stroke. A 5-year-old girl was admitted to the emergency department at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, after experiencing numbness and weakness on her right side and a sudden onset of slurred speech three days before admission. Laboratory findings only showed leukocytosis, while coagulation tests were normal. Non-contrast brain CT revealed an occurrence of cerebral infarction in the left hemisphere. Transcranial Doppler showed no atherosclerosis in cerebral arteries, and carotid Doppler ultrasound results were reported normal. Transthoracic echocardiography showed a PFO with the right-to-left shunt. The patient was treated with an intravenous infusion of citicoline 250 mg twice daily, oral aspirin 80 mg daily, and oral mecobalamin 250 mg daily and was planned to undergo a PFO closure procedure. However, the patient’s parents rejected the plan to perform a PFO closure procedure. PFO has the potential to be a contributing factor to cryptogenic stroke among children. PFO closure followed by antiplatelet therapy for a couple of months has been shown to outperform medical therapy alone. However, additional evaluation should be done to cautiously consider the PFO closure procedure in children.